2021
DOI: 10.4067/s0717-75182021000600852
|View full text |Cite
|
Sign up to set email alerts
|

Efectos de la frecuencia de consumo de alimentos ultraprocesados y su asociación con los indicadores del estado nutricional de una población económicamente activa en México

Abstract: This work aimed to correlate ultra-processed product consumption and nutritional status in a sample of the Mexican labor force population. A cross-sectional study assessed subjects from both genders (18 to 60 years, n=150). Bioimpedance equipment was used to obtain anthropometric measurements and body composition parameters. Moreover, a previously validated frequency questionnaire of ultra-processed foods was used to obtain dietetic data. Results from the nutritional status evaluation indicated that 80% of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 12 publications
0
6
0
3
Order By: Relevance
“…Only fifty percent of Mexican pregnant adolescents in the present study had adequate consumption of energy and macronutrients; similar data has been found in pregnant adults [ 50 ]. This dietary pattern could be a risk factor for developing non-transmissible chronic diseases [ 52 , 53 ] and micronutrients deficiencies [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Only fifty percent of Mexican pregnant adolescents in the present study had adequate consumption of energy and macronutrients; similar data has been found in pregnant adults [ 50 ]. This dietary pattern could be a risk factor for developing non-transmissible chronic diseases [ 52 , 53 ] and micronutrients deficiencies [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…The consumption of free sugars was 34.0% on a daily basis, that is, at least one portion every day, in contrast to 47.0% of daily consumption in the population of the study by Vázquez et al [30]. In another study carried out by Olmedo et al [36] in Argentine adults, the consumption of free sugars from UPF was evaluated and a consumption of up to 36.4% was found, far exceeding the limits established for this critical nutrient.…”
Section: Discussionmentioning
confidence: 57%
“…Regarding the frequency of consumption of processed and UPF, taking into account the critical nutrients of the NOVA classification and the PAHO criteria, the consumption of foods with a high sodium content was moderate to high in 61% of the population, a proportion that exceeds the 8% found in the study by Vázquez et al [30]. In another study conducted by Vargas-Meza et al [31] in a sample of 1,356 Mexican adults regarding sodium intake from foods that were mostly ultra-processed, they showed a daily consumption of 3,132 mg/day, a figure that far exceeds the established intake limit, thus demonstrating that these types of foods are the main source of this critical nutrient.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations